Cultivating Nationalism Through Regional Songs in Early Childhood Education: A Qualitative Exploration and the 4C Pedagogical Model - Paulus Widjanarko; Oka Irmade; Eka Titi Andaryani (Journal of General Education and Humanities, 2026)
In early childhood education, cultivating nationalism and cultural identity requires translating abstract civic values into foundational habits by transforming traditional songs into concrete, multimodal learning experiences. However, there is a pressing need to actively mediate cultural meaning to counterbalance the homogenizing impacts of globalized digital media on young learners. Therefore, this qualitative study investigates the micro-pedagogical mechanisms used to cultivate nationalism and cultural identity through the strategic integration of regional folk songs at Insan Cendekia Kindergarten, Surakarta. The research utilizes a reflexive thematic analysis of practitioner experiences. The empirical findings highlight six key operational themes, spanning from developmentally appropriate planning and authentic assessment to navigating the challenges of digital culture. These mechanisms culminate in the proposed 4C Pedagogical Model: Cultural Contextualization, Corporeal and Multisensory Engagement, Connection of Values to Action, and Continuity between School and Home. The study concludes that the didactic power of regional songs extends far beyond musical performance; its success depends heavily on the educator's ability to mediate cultural meaning actively. Ultimately, this study emphasizes the need to foster a strong school-family ecosystem to mitigate the homogenizing effects of global digital media on early childhood character education.